Breast lesion during lactation diagnosed by fine needle aspiration cytology - Tala, Lubab F. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: The breast function as a secretory gland during pregnancy and lactation due to the interaction of estrogen, progesterone and other pituitary hormones.